OPTIMIZATION AND SOLUBILIZATION STUDY OF NANOEMULSION BUDESONIDE AND CONSTRUCTING PSEUDOTERNARY PHASE DIAGRAM - Puppala, Raman Kumar; A, Vijaya Lakshmi (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of the present study was to formulate and optimize budesonide nanoemulsions for targeting inflammation. Methods: Budesonide is only found in individuals that have used or taken this drug. It is a glucocorticoid used in the management of asthma, the treatment of various skin disorders, and allergic rhinitis. The exact mechanism of the action of budesonide in the treatment of Crohn's disease is not fully understood. However, being a glucocorticosteroid, budesonide has a high local anti-inflammatory effect. The formulation was optimized for different components and the solubility study for the oil in surfactant and cosurfactant mix ratio was optimized using ternary phase diagram. Results: The surfactant mix ratio was optimized as 1:3 where the maximum concentration of the oil has solubilized and the nanoemulsion area was increased. Conclusion: Budesonide nanoemulsion for targeting inflammation and the pseudoternary phase diagram for the solubility studies and the components of different phases were optimized and achieved through this study.